Midregional Proadrenomedullin Predicts Mortality and Major Adverse Cardiac Events in Patients Presenting With Chest Pain: Results From the CHOPIN Trial. (23rd April 2015) - Shah, Kevin S.; Marston, Nicholas A.; Mueller, Christian; Neath, Sean‐Xavier; Christenson, Robert H.; McCord, James; Nowak, Richard M.; Vilke, Gary M.; Daniels, Lori B.; Hollander, Judd E.; Apple, Fred S.; Cannon, Chad M.; et al.
Abstract Objectives Chest pain is a common complaint to emergency departments (EDs) and clinical risk factors are used to predict which patients are at risk for worse outcomes and mortality. The goal was to assess the novel biomarker midregional proadrenomedullin (MR‐proADM) in prediction of mortality and major adverse cardiac events (MACE). Methods This was a subanalysis of the CHOPIN study, a 16‐center prospective trial that enrolled 2, 071 patients presenting with chest pain within 6 hours of onset. The primary endpoint was 6‐month all‐cause mortality and the secondary endpoint was 30‐day and 6‐month MACE: ED visits or hospitalization for acute myocardial infarction, unstable angina, reinfarction, revascularization, and heart failure. Results MR‐proADM performed similarly to troponin (cTnI; c‐statistic = 0.845 and 0.794, respectively) for mortality prediction in all subjects and had similar results in those with noncardiac diagnoses. MR‐proADM concentrations were stratified by decile, and the cohort in the top decile had a 9.8% 6‐month mortality risk versus 0.9% risk for those in the bottom nine deciles (p < 0.0001). MR‐proADM, history of coronary artery disease (CAD), and hypertension were predictors of short‐term MACE, while history of CAD, hypertension, cTnI, and MR‐proADM were predictors of long‐term MACE. Conclusions In patients with chest pain, MR‐proADM predicts mortality and MACE in all‐comers with chest pain and has similar prediction in those with a noncardiac diagnosis. This exploratory analysis is primarily hypotheses‐generating and future prospective studies to identify its utility in risk stratification should be considered.